Relative age effect in volleyball: Does early birth influence elite success? - Kamesh Arul Doss; Gokul Raj; Swamynathan Sanjaykumar; Shinto Vadakkumchery Poulose; Igor Grygus; Yuliya Kalmykova; Priyanka Rana (CV. FOUNDAE, 2026)
Background: The Relative Age Effect (RAE) refers to the unequal representation of athletes according to their birth timing within a selection year. This phenomenon may influence talent identification, athlete development, and access to competitive opportunities. However, limited evidence is available regarding the relationship between RAE, playing-position distribution, and tactical-technical performance among competitive university volleyball players in India. Aims: This study examined the presence of RAE and its association with playing positions and tactical-technical performance among male volleyball players competing at the national inter-university level in Tamil Nadu, India. Methods: A cross-sectional observational design involved 160 male players from universities in Tamil Nadu who participated in national inter-university tournaments during the 2024–2025 season. Participants were classified into four birth quartiles: Q1 (January–March), Q2 (April–June), Q3 (July–September), and Q4 (October–December). Playing positions and performance indicators, including attack efficiency, block success, serve pressure, reception efficiency, and overall performance index, were analyzed using chi-square goodness-of-fit tests and the Kruskal–Wallis test. Results: A significant unequal distribution of players was observed across the birth quartiles (χ² = 10.40, p = 0.015, Cohen’s w = 0.25). Players born in Q1 represented 32.5% of the sample, whereas those born in Q4 accounted for 17.5%, with Q1 players being approximately 1.86 times more likely to be represented than Q4 players. Significant position-specific differences were identified among opposite hitters (χ² = 8.11, p = 0.04) and middle blockers (χ² = 9.02, p = 0.02). However, no significant differences were found across birth quartiles in attack efficiency, block success, serve pressure, reception efficiency, or overall performance index (p > 0.05; η² = 0.008–0.014). Conclusion: RAE remained evident in player representation and positional distribution but was not associated with tactical-technical performance. These findings suggest that birth timing may influence selection opportunities more than actual competitive ability. Talent identification should therefore use multidimensional criteria and prioritize athletes’ long-term developmental potential rather than age-related physical advantages.